Bridging Emotional Intelligence and Problem solving Ability: A Case Study on the Sandwich Generation - Ismanto, Dhea; Hurriyati, Dwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The sandwich generation is recognized as a group with dual responsibilities, namely fulfilling the needs of both children and parents simultaneously. This condition often leads to significant financial and emotional pressures. This study aims to analyze the relationship between emotional intelligence and problem-solving abilities among retail store employees in the sandwich generation in Seberang Ulu, Palembang. The research employs a quantitative correlational method involving 147 respondents selected using purposive sampling techniques. Data were collected using emotional intelligence and problem-solving scales, analyzed through simple regression tests. The results indicate a significant relationship between emotional intelligence and problem-solving abilities, with a correlation coefficient of R = 0.577 (p < 0.01) and an emotional intelligence contribution of 33.3% to problem-solving. These findings suggest that individuals with high emotional intelligence tend to be more effective in addressing problems. The implications of this study highlight the importance of training and interventions to develop emotional intelligence in the workplace, enhancing the problem-solving abilities of the sandwich generation so they can adapt better to the pressures and demands of dual roles. Generasi sandwich dikenal sebagai kelompok yang memiliki tanggung jawab ganda, yaitu memenuhi kebutuhan anak-anak dan orang tua secara bersamaan. Kondisi ini seringkali memunculkan tekanan finansial dan emosional yang signifikan. Penelitian ini bertujuan untuk menganalisis hubungan antara kecerdasan emosional dan kemampuan pemecahan masalah pada pegawai toko retail generasi sandwich di Seberang Ulu, Palembang. Penelitian menggunakan metode kuantitatif korelasional dengan melibatkan 147 responden yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui skala kecerdasan emosional dan problem solving, yang dianalisis menggunakan uji regresi sederhana. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara kecerdasan emosional dan problem solving dengan koefisien korelasi R = 0,577 (p < 0,01) dan kontribusi kecerdasan emosional sebesar 33,3% terhadap problem solving. Temuan ini menunjukkan bahwa individu dengan kecerdasan emosional tinggi cenderung lebih efektif dalam menghadapi masalah. Implikasi dari penelitian ini menyoroti pentingnya pelatihan dan intervensi pengembangan kecerdasan emosional di tempat kerja untuk meningkatkan kemampuan pemecahan masalah generasi sandwich, sehingga mereka dapat lebih adaptif dalam mengelola tekanan dan tuntutan peran ganda.